Nutritional potential of selected species of Arisaema Mart. from Nepal (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Dhakal L, Aryal B, Joshi GP, Pant DR. 2020. Nutritional potential of selected species of Arisaema Mart. from Nepal. Biodiversitas 21: 5703-5709. Species of Arisaema Mart. are believed to be poisonous, but few species are used as food in different communities. Therefore, an assessment of nutritional properties of six selected taxa of Arisaema including three edible taxa was made in order to find out their nutritional potential. Methanolic or aqueous extracts of samples (rhizomes and aerial parts) were analyzed for various nutritional and anti-nutritional parameters. On nutritional basis, the total starch content and total reducing sugar were found highest (25.71±0.04mg/g powder) and (46.73±0.06 mg/g extract), respectively in aerial parts of A. echinatum. Total protein and phosphorus content was highest in rhizome of A. tortuosum var. curvatum. Similarly, extracts of aerial parts of A. tortuosum var. curvatum also possessed highest amount of total phenolic content (52.67±0.24mg GAE/g), total flavonoid content (14.13 ± 0.03 mg QE/g), and also demonstrated best antioxidant activity (IC50, 108.59±0.54 µg/mL) in terms of DPPH radical scavenging activity among the selected taxa. Inhibition of ?-amylase and ?-glucosidase in vitro was found to be highest (78.82 %) in rhizome extracts of A. echinatum and extracts of aerial parts of A. concinnum (34.82 %), respectively.
Keywords: Antioxidant activity, anti-nutrients, Arisaema, nutritional value